Untangling the semantic web the straightforward way to give more meaning to the web. - Cavanaugh, Erin
The Semantic Web is a hot topic in information circles today, and its adoption will largely depend on stakeholders understanding its potential benefits and tools vendors providing an easy entry for developers to learn and work with its related technologies.